2011
DOI: 10.1080/13854046.2011.565076
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Neuropsychological Outcome After Mild Traumatic Brain Injury: Re-analyses and Reconsiderations of Binder et al. (1997), Frencham et al. (2005), and Pertab et al. (2009)

Abstract: The meta-analytic findings of Binder et al. (1997) and Frencham et al. (2005) showed that the neuropsychological effect of mild traumatic brain injury (mTBI) was negligible in adults by 3 months post injury. Pertab et al. (2009) reported that verbal paired associates, coding tasks, and digit span yielded significant differences between mTBI and control groups. We re-analyzed data from the 25 studies used in the prior meta-analyses, correcting statistical and methodological limitations of previous efforts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
225
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(245 citation statements)
references
References 42 publications
16
225
2
2
Order By: Relevance
“…Consistent with previous research suggesting a time-limited course of impairment following conventional concussive injuries (cf. Rohling et al, 2011), present results suggest that BRC does not in and of itself contribute to cognitive impairment months or years following injury. Veterans with remote histories of BRC should anticipate favorable long-term cognitive prognosis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with previous research suggesting a time-limited course of impairment following conventional concussive injuries (cf. Rohling et al, 2011), present results suggest that BRC does not in and of itself contribute to cognitive impairment months or years following injury. Veterans with remote histories of BRC should anticipate favorable long-term cognitive prognosis.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, results of at least one longitudinal study of OEF/OIF cohorts suggest that the deployment process itself may be associated with cognitive limitations (Vasterling et al, 2006). Additionally, comparison of an OEF/OIF concussion sample with an OEF/OIF non-concussion sample will allow for direct examination of long-term impairments that may be associated with BRC, or alternatively define whether outcomes mimic favorable long-term outcomes reported in civilian concussion samples (Belanger, Curtiss, Demery, Lebowitz, & Vanderploeg, 2005;Frencham, Fox, & Maybery, 2005;Iverson, 2005;McCrea et al, 2005;Rohling et al, 2011;Schretlen & Shapiro, 2003). Results of the latter studies suggest that cognitive impairment associated with concussion is time-limited; the great majority of individuals attain baseline function within days, weeks, to no more than a few months post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size (N) of mTBI (range: 264 -3,801) and control participants (range: 176 -5,631) fluctuated across quantitative reviews. Among the limited studies reporting demographics of their samples (i.e., Broglio & Puetz, 2008;Frencham et al, 2005;Rohling et al, 2011;Zakzanis et al, 1999), mean reported age (range: 19 -35) and percent of male participants (range: 64 -92.9) differed considerably across reviews. Notably, the only sports-related mTBI metaanalysis reporting sample demographics involved the youngest and most male sample (Broglio & Puetz, 2008).…”
mentioning
confidence: 99%
“…Despite the prevalence and public concern surrounding mTBI, past researchers have dismissed its long-term neuropsychological impact as clinically insignificant Frencham, Fox, & Maybery, 2005;Larrabee, Binder, Rohling, & Ploetz, 2013;Rohling et al, 2011; Shretlen & Shapiro, 2003); however, some individuals may remain symptomatic long after the concussive event (Bigler et al, 2013;Pertab, James, & Bigler, 2009), potentially explained by acute neurological impairment that can persists after injury (e.g., Cohen et al, 2007;Holli et al, 2010). Alternatively, some researchers have identified more psychogenic predictors of persistent symptoms (Silverberg & Iverson, 2011).Persistent symptoms of mTBI remain a contentious issue, with a recent scholarly dialogue closely examining the evidence both for and against their existence (Bigler et al, 2013;Larrabee et al, 2013;Pertab et al, 2009;Rohling et al, 2011). Dating back to the 19th century, scholars have argued between the psychological and physiological etiologies of post-mTBI symptoms (see Binder et al, 1997).…”
mentioning
confidence: 99%
“…The majority (up to 90%) of TBIs are mild (Langlois, Keglar et al 2003;Langlois, Rutland-Brown et al 2006), and while most cases recover fully within three months (Rohling, Binder et al 2011), a significant proportion report on-going difficulties. Depression is the most commonly reported psychiatric consequence of TBI, with reports suggesting that up to 60% of patients with TBI develop depression within 12 months of injury, even following a mild injury (Busch 1998;Hibbard, Uysal et al 1998;Fann, Uomoto et al 2000;Robinson and Jorge 2005;Hoge 2008).…”
Section: Introductionmentioning
confidence: 99%